2017
DOI: 10.2135/cropsci2016.11.0937
|View full text |Cite
|
Sign up to set email alerts
|

The Genes Bm2 and Blmc that Affect Epicuticular Wax Deposition in Sorghum are Allelic

Abstract: Epicuticular waxes (EW) coat the aerial surfaces of the sorghum [Sorghum bicolor (L.) Moench] plant and have a role in the plant's resistance to abiotic and biotic stresses, such as drought, ultraviolet light, insects, and fungal pathogens. Mutants of the Bloomless2 (Bm2) locus, such as bm2‐3, lack visible EW and have inhibited synthesis of the cuticle. The sorghum mutant bloom‐cuticle (blmc) also lacks visible EW and has inhibited synthesis of the cuticle, as well as many other effects. In this study, an alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Another locus, BLMC (BLooMCuticle) responsible for the production of profuse wax in sorghum was identified from a population derived from BTx623 (profuse wax donor), and KFS2021 (sparse wax) (Burow et al 2009). Further allelism test revealed that BLMC is allelic to Bm2 (Punnuri et al 2017). A genomic region associated with bloom inhibition (bloomless trait) has been identified from the gamma-irradiated mutant populations (Mizuno et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another locus, BLMC (BLooMCuticle) responsible for the production of profuse wax in sorghum was identified from a population derived from BTx623 (profuse wax donor), and KFS2021 (sparse wax) (Burow et al 2009). Further allelism test revealed that BLMC is allelic to Bm2 (Punnuri et al 2017). A genomic region associated with bloom inhibition (bloomless trait) has been identified from the gamma-irradiated mutant populations (Mizuno et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that wax bacteria, including Sphingomonas, Rhizobium, and Pseudomonas species play role in plant drought resistance as shown in root compartments (Luo et al 2019;Igiehon et al 2019;Mahmoudi et al 2019;Hone et al 2021). To gain further insight into epicuticular wax microbiome assembly and dynamics, next steps could expand this research not only by including samples from different growing seasons, but also by including sorghum genotypes that are mutants in wax production (Jenks et al 1994(Jenks et al , 2000bPeters et al 2009;Punnuri et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The sorghum genotypes used in this study were the Bm2 mutants bm2 (allelic designation bm2‐1 ), bm6 ( bm2‐2 ), bm22 ( bm2‐3 ), bm33 ( bm2‐4 ), and bloom cuticle ( blmc ) ( bm2‐7 ) (Peters et al., 2009; Punnuri et al., 2017). Mutants will be described by their allelic designations hence forth.…”
Section: Methodsmentioning
confidence: 99%
“…In this study we examined the sorghum Bm2 locus, a locus that effects epicuticular wax and cuticle deposition (Jenks et al., 1994). The Bm2 locus is the best characterized bloomless locus with seven alleles, bm2‐1 to bm2‐7 (Jenks et al., 2000; Peters, Jenks, Rich, Axtell, & Ejeta, 2009; Punnuri, Harris‐Shultz, Knoll, Ni, & Wang, 2017). Mutants in the Bm2 gene have many pleiotropic effects including significant reductions in the amount of C 28 and C 30 fatty acids, rapid leaf water loss rates, leakier epidermal layers, and higher susceptibility to a fungal pathogen (Burow, Franks, & Xin, 2008; Jenks et al., 1994).…”
Section: Introductionmentioning
confidence: 99%